Identifying Patient Satisfaction Determinants in Hemodialysis Settings: A Systematic Review - Al Nuairi A; Bermamet H; Abdulla H; Simsekler MCE; Anwar S; Lentine KL (Dove Medical Press, 2022)
Arwa Al Nuairi,1 Hala Bermamet,1 Hind Abdulla,1 Mecit Can Emre Simsekler,1 Siddiq Anwar,2 Krista L Lentine3 1Department of Industrial and Systems Engineering, Khalifa University of Science and Technology, Abu Dhabi, 127788, United Arab Emirates; 2Sheikh Shakhbout Medical City, Abu Dhabi, 10001, United Arab Emirates; 3Saint Louis University Center for Abdominal Transplantation, St. Louis, MO, USACorrespondence: Mecit Can Emre Simsekler, Khalifa University of Science and Technology, Department of Industrial and Systems Engineering, P.O. Box 127788, Abu Dhabi, United Arab Emirates, Tel +9712 312 4058, Fax +971 2 447 2442, Email emre.simsekler@ku.ac.aePurpose: Patient satisfaction is a measure of care quality that assists providers in determining the effectiveness of their services while meeting patients' expectations. This study aimed to review existing studies that have focused on patients' satisfaction determinants in Hemodialysis (HD) settings.Methods: Electronic databases (PubMed, ScienceDirect, Scopus, and Google Scholar) were searched from 2000 onwards to identify studies using search terms related to patient satisfaction and hemodialysis centers. Article review was limited to studies written in English. A total of 19 articles were included by following the PRISMA statement. Data were extracted using a structured form and summarized in a tabular format to identify different determinants that showed a relationship with patient satisfaction. Determinants were classified into provider-related determinants and patient-related characteristics.Results: Provider-related determinants of patient satisfaction in HD centers include staff, facility, service, and treatment. Patient-related characteristics associated with satisfaction include demographics and health status history. Based on this systematic review, key correlates of patient satisfaction in hemodialysis centers include: staff, facility, service, treatment, patient's demographics, and health status.Conclusion: The findings of this study can help healthcare facilities in taking measures in line with the specified determinants to enhance patient satisfaction and improve the organizational performance of the healthcare centers. It is important to constantly study and improve these determinants based on patient feedback to improve patient satisfaction and quality of care.Keywords: hemodialysis patients, patient satisfaction, patient experience, healthcare quality